UNEP at work. Costing the gender gap - United Nations Environment Programme (Our Planet, 2017)
Women form a large proportion of the agricultural labour force in sub-Saharan Africa and play a vital role in ensuring family nutrition and food security. But gender-based inequalities in access to and control of productive and financial resources are inhibiting agricultural productivity and reducing food security. At the same time, a changing climate means that there is a shrinking window to close the gender gap in agriculture and seize the prospects for promoting women’s empowerment, economic development and resilience to shocks.